난치성 창상에 음압치료의 적용 - 정현균(Heun Guyn Jung); 기성찬(Sungchan Ki); 김병학(Byunghak Kim); 김관우(Kwanwoo Kim); 김영경(Yungkyung Kim); 조유경(Yungkyung Kim); 최용수(Yongsoo Choi) (The journal of the Korean Orthopaedic Association, 2012)
목적: 난치성 창상치료에 있어 기존 시행되던 드레싱과 음압을 이용한 드레싱을 비교하여 음압치료의 유용성을 알아보고자 하였다. 대상 및 방법: 2008년 1월부터 2009년 12월까지 음압치료를 시행한 20예와 같은 기간 통상적 드레싱을 시행한 20예를 대상으로 하여 상처 크기 변화, 육아조직 생성 정도, 창상 치유기간에 대해 조사하였다. 결과: 상처 크기 변화는 음압치료군이 평균 60.2±59.1 cm2에서 29.7±18.8 cm2로 대조군은 평균 60.3±83.3 cm2에서 34.4±47.6 cm2로감소하였으나 두 군 간 차이를 보이지 않았다(p=0.147). 육아조직 형성 정도는 음압치료군이 평균 1.2±0.4에서 2.7±0.6, 대조군은 1.2±0.4에서 2.4±0.5로 호전을 보였으나 통계학적 차이는 없었다(p=0.192). 창상 치유기간은 최초 변연 절제술 후 음압치료군이 17.5±8.3일,대조군은 22.9±22.0일이 소요되었다(p=0.857). 결론: 난치성 창상에 음압치료는 상처 크기 감소, 육아조직 형성 및 창상 치유기간에 통상적인 치료법과 같이 양호한 결과로 의료 인력 분담의 장점을 고려할 때 통상적인 창상치료를 대체할 수 있는 부가적인 창상치료법으로 이용될 수 있으리라 생각한다. Purpose: We analyzed the usefulness of vacuum-assisted closure (VAC) dressing to facilitate the healing of diffi cult wounds by comparing the results of conventional dressings. Materials and Methods: We selected 20 cases for the experimental group (VAC group) and 20 cases for the control group (conventional dressing), and investigated the change in wound size, formation of granulation tissue, and duration of wound healing in the two groups. Results: In the VAC group, the size of wound decreased from 60.2±59.1 cm2 to 29.7±18.8 cm2 (p=0.001). In the control group, it decreased from 60.3±83.3 cm2 to 34.4±47.6 cm2 (p=0.04). For formation of granulation, it increased from 1.2±0.4 to 2.7±0.6 (p=0.001)in the VAC group and from 1.2±0.4 to 2.4±0.5 in the control group. For the duration of healing, it took 17.5±8.3 days for the VAC group and 22.9±22.0 days in the control group (p=0.857). However there were no statistically signifi cant differences in all the parameters between the 2 groups (p>0.05). Conclusion: The clinical application of VAC to difficult wound yield comparable results in terms of a decrease in wound size,formation of granulation, and the duration of healing. VAC dressing could be an alternative treatment option for a diffi cult wound considering the advantage of saving medical human resources. KCI Citation Count: 1